1986
DOI: 10.1111/j.1528-1157.1986.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in the Elderly: Incidence, Social Function, and Disability

Abstract: The incidence of epilepsy in persons greater than or equal to 60 years was studied during a 5-year period in an urban area. The incidence of patients with definite epilepsy was 77 new cases per year per 100,000 citizens greater than 60 years of age, with a significant excess of male patients. Generalized and partial seizures each accounted for about half of the seizures, but the majority of patients experienced generalization at least once. Of 163 patients with onset of epilepsy during the study period, 152 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 22 publications
5
37
2
4
Order By: Relevance
“…Of the one to one-and-a-half year survivors in our study, 34% had had recurrent seizure, which is a little higher than other studies, which have reported recurrent seizures ranging from 11% to 28% in one to one-and-a-half years follow up. 4,9 Of those patients with a previous history of stroke in our study, recurrent seizures recurred in more than 72% similar to the rate as reported by Luhdorf, et al 10 in which there was seizure recurrence in more than 80% of elderly patients with a history of stroke. Status epilepticus de novo frequently occurs in the elderly with no prior history of epilepsy and represents a considerable risk for the subsequent development of epilepsy.…”
Section: Resultssupporting
confidence: 76%
“…Of the one to one-and-a-half year survivors in our study, 34% had had recurrent seizure, which is a little higher than other studies, which have reported recurrent seizures ranging from 11% to 28% in one to one-and-a-half years follow up. 4,9 Of those patients with a previous history of stroke in our study, recurrent seizures recurred in more than 72% similar to the rate as reported by Luhdorf, et al 10 in which there was seizure recurrence in more than 80% of elderly patients with a history of stroke. Status epilepticus de novo frequently occurs in the elderly with no prior history of epilepsy and represents a considerable risk for the subsequent development of epilepsy.…”
Section: Resultssupporting
confidence: 76%
“…1 Epilepsy, defined as at least 2 unprovoked seizures occurring .24 hours apart, 2 is a common neurologic disorder in this age group. 3 While multiple studies have reported the prevalence and incidence of epilepsy in older adults, [4][5][6] their findings have limited generalizability. One recent study addressed the limited generalizability of prior studies by using outpatient administrative claims codes from the Centers for Medicare & Medicaid Services (CMS), which includes use data for .95% of the older adult US population.…”
mentioning
confidence: 99%
“…In Minnesota, 55% of all new cases of seizures in persons older than 65 were attributed to the acute or late effects of cerebrovascular disease [2,3]. Embolic strokes, intracerebral hemorrhages, and arteritis are the cerebrovascular diseases most often associated with seizures in this age-group [18,[31][32][33]. Seizures occur in 2.2-25% of patients with acute strokes [34][35][36][37], and in 3-8% of the cases as a chronic complication of strokes [37,38].…”
Section: Etiologymentioning
confidence: 99%